Sulfuretin, a natural Src family kinases inhibitor for suppressing solar UV-induced skin aging. (January 2019) - Han, Ahram; Lee, Jinhyuk; Lee, Myung-hee; Lee, Sung-Young; Shin, Eun Ju; Song, Young-Ran; Lee, Kwang Min; Lee, Ki Won; Lim, Tae-Gyu
Graphical abstract: Highlights: The anti-wrinkle formation activity of sulfuretin was suggested. Sulfuretin acts as general Src family kinase inhibitor. The expected interaction was assumed using computer modeling. Abstract: This study suggests sulfuretin as an ant-skin aging agent. Sulfuretin significantly reduces solar UV (sUV)-increased matrix metalloproteinase-1 (MMP-1) expression and c-Jun phosphorylation in human dermal fibroblasts as well as skin tissue. An examination of the underlying mechanisms showed that sUV-activated MAPK signaling pathways are blocked by sulfuretin. Interestingly, sulfuretin directly inhibits the kinase activity of selected Src family. Because the amino acid sequence of Hck kinase which used kinase array is 230–497, it was assumed that sulfuretin interacts with this conserved domain of Src family kinase. It was also found that sulfuretin directly binds to sulfuretin with the lowest binding energy of −8.9 kcal/mol and free energy of −10.07 kcal/mol. Additionally, Hck protein was precipitated with sulfuretin-conjugated Sepharose 4B beads in HDFs cell lysate. Overall, present findings indicated that sulfuretin plays the role of anti-skin aging agent by acting as a general Src family kinase inhibitor in human skin.